Monitoring dissolved active trace elements in biogas plants using total reflection X‐ray fluorescence spectrometry. (31st March 2020) - Arthur, Richard; Scherer, Paul A.
Abstract : Generally, full‐scale biogas plants require trace elements supplementation to sustain a stable process. The aim was to apply total reflection X‐ray fluorescence (TXRF) to monitor the dissolved, active elements, for the first time, at μg/L levels in biogas plants. The digester liquid is comparable to sludge with high solids content and high salt concentrations. The ions are usually measured in the dried fermenter slurry after acid digestion in its inactive bound form, although microorganisms can take up only dissolved ions as active agent. In this study, a procedure was developed to monitor dissolved ions in such environmental processes to prevent an overdose or underdose. The analytical figures of merit considered were the lowest possible limit of detection, the recovery of spiked ions and linearity. Samples were spiked with nickel, selenium and tungsten in the range of 10–200 μg/L. Highest recovery rates of >93% for concentrations of 10 to <100 μg/L were obtained after the samples were centrifugated twice, followed by application of microwave‐assisted acid digestion. The calculated lowest limit of detection was 2–4 μg/L. The developed method was first tested in laboratory‐scale biogas digesters with wheat straw as substrate. Successful application of TXRF was also achieved in a full‐scale biogas plant to estimate the dynamics of "active" trace element ions in the range of 2–1, 000 μg/L for several months. Therefore, cost‐effective biogas plant management is possible through the application of TXRF spectrometry to monitor trace elements.